Highly Deformed o‐Carborane Functionalised Non‐linear Polycyclic Aromatics with Exceptionally Long C−C Bonds. Issue 6 (23rd December 2020) - Marsh, Adam V.; Little, Mark; Cheetham, Nathan J.; Dyson, Matthew J.; Bidwell, Matthew; White, Andrew J. P.; Warriner, Colin N.; Swain, Anthony C.; McCulloch, Iain; Stavrinou, Paul N.; Heeney, Martin
Abstract: The effect of substituting o ‐carborane into the most sterically hindered positions of phenanthrene and benzo(k)tetraphene is reported. Synthesised via a Bull–Hutchings–Quayle benzannulation, the crystal structures of these non‐linear acenes exhibited the highest aromatic deformation parameters observed for any reported carborane compound to date, and among the largest carboranyl C−C bond length of all organo‐substituted o ‐carboranes. Photoluminescence studies of these compounds demonstrated efficient intramolecular charge‐transfer, leading to aggregation induced emission properties. Additionally, an unusual low‐energy excimer was observed for the phenanthryl compound. These are two new members of the family of carborane‐functionalised non‐linear acenes, notable for their peculiar structures and multi‐luminescent properties. Abstract : o ‐Carborane‐functionalised phenanthrene and benzo(k)tetraphene are reported in this work; two highly sterically hindered structures, with the latter displaying the largest aromatic deformation parameters of any organo‐substituted o ‐carborane compound, and amongst the longest carboranyl C−C bond. Functionalisation of these polycyclic aromatic hydrocarbons induces stimuli‐responsive luminescence properties, including aggregation‐induced emission.